PERANCANGAN KEAMANAN JARINGAN PADA BANK SULSELBAR PAREPARE - Rakhmadi Rahman; Julistio Fadjar Anugrah Sao (CV. Denasya Smart Publisher, 2024)
This research discusses the implementation of computer networks at Bank Sulselbar Parepare branch to improve operational efficiency and data security. Using the Cisco Packet Tracer application, network topology design involves the use of switches to manage data traffic, PCs for communication between devices, and servers connected to Cisco switches to ensure easy access to critical services. Static IP address settings ensure reliable connections, while firewalls on servers secure the network from unauthorized access and cyberattacks. Test results show significant improvements in network security and efficiency, as well as improved service quality and customer satisfaction. This implementation succeeded in meeting the objectives of improving operational performance and data security at the bank.